Longitudinal case study of child-directed speech in Slovak from the perspective of acquisition of personal pronouns - Walková, Milada; Brestovičová, Alexandra (Československá psychologie, 2021)
Objectives. Previous research has shown that the acquisition of personal pronouns benefits from input with higher amounts of stable reference. This paper aims to provide more evidence of how input is structured. The language under study is Slovak, a pro-drop language, allowing to extend the study of input to verb marking. Participants and setting. The longitudinal study follows speech directed to three children in two families from the age 1;9 to 3;0. Hypotheses. It was hypothesised that the incidence of the first and second person singular pronouns and verb marking as expressions with shifting reference grows with the child’s age while the incidence of proper names and category names as expressions with stable reference decreases with the child’s age. Statistical analysis. Occurrences of first and second person singular pronouns and verb marking as expressions with shifting reference as well as proper names and category names referring to the speaker and addressee as expressions with stable reference were found and analysed. Simple regression analysis testing was conducted on the data. Results. The results confirm the hypothesis, showing an increase in the first and second person singular pronouns and verb marking over time, at the expense of proper names and category names referring to the speaker and the addressee. Study limitations. The study is limited by the size of the sample.
Keywords: Research; Child Language; výzkum; Language Development; Child; lidé; dítě; dětská řeč; vývoj řeči; Humans